Comparison of Muscle Strength in Stroke Patients between The Given and Not Given Range of Motion Exercise - Rhestifujiayani, Eka; Huriani, Emil; Muharriza, Muharriza (Department of Nursing, Faculty of Medicine, Diponegoro University, 2015)
Background: Hemiparesis is a common problem that can caused disability. ROM Exercise is an exercise that to performed evaluate and to improv the function of the musculoskeletal system and is one of therapies in stroke patients that aim to increase cerebral blood flow, minimize disability caused by stroke, so can refine sensory motoric function.Purpose: The objective of this study was to examine the effect ROM exercises of the extremity muscle strength in patients with stroke Methods: This study was a quasi experimental with non equivalent control group design. The sampling technique was purposive sampling. The number of sample was 20 respondents. The statistical test used are Wilcoxon test and Mann-Whitney test. Result: Wilcoxon test in control group showed p-value in upper extremities was p=0,157 and in lower extremities was p=0,083, it mean that there was no increase in muscle strength in the control group and in experiment group showed p-value in upper extremities was p=0,004 and in lower extremities was p=0,005, it mean that there is increase in muscle strength in the experiment group. The result of Mann-Whitney test showed p-value in upper extremities was p=0,002 and in lower extremities was p=0,006, it means that there were differences in the increase in muscle strength between control group and experiment group. Conclusion: ROM exercises affect the increase in muscle strength in stroke patients with hemiparesis. The ROM exercises can be used as a nursing intervention in the provision of nursing care.